The Empowerment of Consumers with Disabilities: The Role of Self-Esteem, Accessibility, and Access to Information - Simanjuntak, Megawati; Rahmi, Fauzia; Dewi, Santi Utami (ASEAN Marketing Journal, 2024)
Consumer empowerment in Indonesia remains relatively low, particularly for individuals with disabilities. This study investigates the roles of accessibility, self-esteem, and information access in empowering disabled consumers. A total of 100 participants with physical disabilities, aged 17 and older, were surveyed regarding their online and offline purchasing experiences. Data were collected via an online questionnaire and analyzed using SEM PLS. Results indicate that self-esteem and information accessibility significantly influence the empowerment of consumers with disabilities, with the Disabled Consumer Empowerment Index categorized as "not empowered." Notably, the knowledge dimension received the lowest scores based on a traffic-light system. These findings suggest that consumer protection agencies should collaborate with the government to enhance the self-determination rights of disabled consumers in Indonesia. This study contributes to the literature by emphasizing the critical factors of self-esteem, accessibility, and information access in the empowerment of consumers with disabilities.